2021
DOI: 10.1002/ange.202108996
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymers Based on Ethylene and Methacrylates Using a Combination of Catalytic Chain Transfer Polymerisation (CCTP) and Radical Polymerisation

Abstract: Twos calable polymerisation methods are used in combination for the synthesis of ethylene and methacrylate blockc opolymers. w-Unsaturated methacrylic oligomers (MMA n )produced by catalytic chain transfer (co)polymerisation (CCTP) of methyl methacrylate (MMA) and methacrylic acid (MAA) are used as reagents in the radical polymerisation of ethylene (E) in dimethyl carbonate solvent under relatively mild conditions (80 bar,7 0 8 8C). Kinetic measurements and analyses of the produced copolymers by sizee xclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In academic research, D'Agosto has shown how PMMA reactive oligomers can be used to make PE- b -PMMA block copolymers be effectively acting as a radical chain stopper in the radical polymerisation of ethene in both solution and emulsion. 18,19 When added to radical polymerisation of less reactive methacrylates they undergo very efficient RAFT to give multi block polymethacrylates again in both solution and emulsion polymerisation conditions. 20 The capabilities of these reactive oligomers has also been demonstrated by application in soap-free emulsion polymerization in the synthesis of functional nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In academic research, D'Agosto has shown how PMMA reactive oligomers can be used to make PE- b -PMMA block copolymers be effectively acting as a radical chain stopper in the radical polymerisation of ethene in both solution and emulsion. 18,19 When added to radical polymerisation of less reactive methacrylates they undergo very efficient RAFT to give multi block polymethacrylates again in both solution and emulsion polymerisation conditions. 20 The capabilities of these reactive oligomers has also been demonstrated by application in soap-free emulsion polymerization in the synthesis of functional nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, D'Agosto et al synthesized block copolymers of ethylene and methyl methacrylate on the basis of CCTP and FRP (M w up to 180 kg mol −1 ). 62 Nevertheless, chain shuttling polymerization (CSP) is a distinct CCTP technique best suited for synthesizing olefin block copolymers. In 2006, Dow announced the industrial production of ethylene−octene olefin block copolymers (OBCs) via CSP in the presence of diethyl zinc as a chain shuttling agent (CSA).…”
Section: Introductionmentioning
confidence: 99%
“…The use of compounds based on olefins as a plasticizer comonomer for the production of high-impact copolymer based on styrene and methyl methacrylate is considered an important area of research [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%